Integral logistics management operations and supply chain management within and across companies - Schönsleben, Paul (CRC Press, 2016)
Integral Logistics Management: Operations and Supply Chain Management Within and Across Companies, Fifth Edition prepares students to tackle the logistical, planning, and managerial challenges they'll face on the job. It covers both the theoretical and practical aspects of the differing characteristics, tasks, methods, and techniques of planning and control in company logistics